2018
DOI: 10.14254/2071-789x.2018/11-4/15
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of teachers from public and private sector universities in Lahore, Pakistan: A comparative study

Abstract: Pakistan. A comparative study has been carried out, based on the survey method using a quantitative approach. Data were collected from a questionnaire completed by 345 Teachers (203 from public and 142 from private sector), from 10 universities (5 public and 5 private), using convenience sampling. The results of the Chi-Squared independence hypothesis test reveal statistically significant differences in degree of agreement for some of the statements between the Public and Private University Teachers on the Job… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…This factor is related to the possibilities of job advancement, training, and expectations of a career path (Figure 2c). The present research outcomes are aligned with the findings obtained in a comparative study on public and private university professor's job satisfaction carried out in Pakistan, in which when asked about the opportunity to be promoted for doing their job well; A significant relationship was found, and adjusted standardized residuals examinations clear that the highest proportion of agreement among the professors of the public university contributed to the significance of the results (Hameed et al, 2018). The factor related to relationships with superiors is a higher level of satisfaction in privately managed institutions.…”
Section: Figure 2 the First Block Of Differences In Determinants Of Job Satisfaction Between Public And Private Institutionssupporting
confidence: 85%
“…This factor is related to the possibilities of job advancement, training, and expectations of a career path (Figure 2c). The present research outcomes are aligned with the findings obtained in a comparative study on public and private university professor's job satisfaction carried out in Pakistan, in which when asked about the opportunity to be promoted for doing their job well; A significant relationship was found, and adjusted standardized residuals examinations clear that the highest proportion of agreement among the professors of the public university contributed to the significance of the results (Hameed et al, 2018). The factor related to relationships with superiors is a higher level of satisfaction in privately managed institutions.…”
Section: Figure 2 the First Block Of Differences In Determinants Of Job Satisfaction Between Public And Private Institutionssupporting
confidence: 85%
“…Academics staff will lay more effect on working, and it will help the organization to produce more and higher quality employee graduates (Yee, 2018). Moreover, Hameed, Ahmed-Baig, and Cacheiro-González, (2019), informed that there are multiple reasons for teacher's job satisfaction which include recognition, responsibility, achievement, motivation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in education industry the most contributing factor to dissatisfaction or satisfaction is teacher's job security (Oshagbemi, 1997) and sense of encouragement and appreciation is also important for teacher's satisfaction (Lankveld, Schoonenboom, Volman, Croiset & Beishuizen, 2017;Hameed, et al (2019). On the similar note a study conducted on 406 teachers from public sector colleges in the Punjab -Pakistan, found that job satisfaction is largely due to intrinsic motivational reasons, which include recognition, promotions, and opportunities to acquire new skills (Nadim, Chaudhry, Kalyar, & Riaz, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The instructors influence and inspire the thoughts of the learners. According to Hameed, Baig, and Cacheiro-González (2018), teachers are mostly exciting element when we attain teaching as a system. Education is the development of structuring the states by providing cultured associates of humanity.…”
mentioning
confidence: 99%